2004
DOI: 10.1063/1.1638620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on carbon nanotube diameter and bundle arrangement: Microscopic and macroscopic analysis

Abstract: The diameter distribution of the nanotubes produced by electric-arc discharge are measured using Raman spectroscopy at various wavelengths. These measurements agree with the results provided by two other techniques: high-resolution transmission electron microscopy and x-ray diffraction. The mean tube diameter shifts more than 0.1 nm with the increase of argon in the inert atmosphere. Some argon concentrations favored the synthesis of metallic tubes with specific diameters. Furthermore, the background gas influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Although the mechanism of the formation and growth of SWNTs in an arc discharge was studied for a decade, location of the region in arc discharge in which SWNT synthesis occurs and the temperature range favourable for SWNT growth remains unclear. According to some authors [29,50] the nanotube formation occurs on the periphery of an arc column at a moderate temperature range 1200-1800 K while other studies suggested that the cathode sheath adjacent to the hot arc column (∼5000 K) is the arc region where the nanotube growth occurs [63][64][65]. Recall that in the cathode sheath region, the temperature might be well above the reported critical temperatures of thermal stability of the nanotubes.…”
Section: Why It Is Difficult To Control the Synthesis ?mentioning
confidence: 99%
“…Although the mechanism of the formation and growth of SWNTs in an arc discharge was studied for a decade, location of the region in arc discharge in which SWNT synthesis occurs and the temperature range favourable for SWNT growth remains unclear. According to some authors [29,50] the nanotube formation occurs on the periphery of an arc column at a moderate temperature range 1200-1800 K while other studies suggested that the cathode sheath adjacent to the hot arc column (∼5000 K) is the arc region where the nanotube growth occurs [63][64][65]. Recall that in the cathode sheath region, the temperature might be well above the reported critical temperatures of thermal stability of the nanotubes.…”
Section: Why It Is Difficult To Control the Synthesis ?mentioning
confidence: 99%
“…According to previous work, 30,45 the nanotube formation occurs on the periphery of an arc column at a moderate temperature range of 1200-1800 K. Other studies suggested that it is the cathode sheath adjacent to hot arc column ͑ϳ5000 K͒ is the arc region where the nanotube growth occurs. [45][46][47][48] Recall that in the cathode sheath region, the temperature might be well above the reported critical temperatures of thermal stability of the nanotubes. In this respect, a question about possible carbon nanotube growth in cathode sheath region remains open.…”
Section: Introductionmentioning
confidence: 96%
“…The chirality and architecture of CNTs are very sensitive to the conditions of preparations. However, most of these methods are relatively expensive with low yield, necessitating bulk handling systems to produce sizeable quantity of CNTs [5][6][7]. In addition to the low cost and high yield, high purity and consistent size are some of the important quality requirements which are essential for wide scale proliferation of CNTs.…”
Section: Introductionmentioning
confidence: 99%